Factors that Influence Drop Out of Vocational High School - Triyani Lestari; Andryan Setyadharma (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of this study is to analyze the factors that influence the likelihood of students dropping out of school in Pekalongan City. The sample in this study was 100 ex-students vocational school in Pekalongan City. Data were obtained from the questionnaire using the convience sampling. The method used in this study is quantitative with logit analysis. The results of the study showed that perception, number of siblings, helping parents, problems with friends, and punishments had a significant effect on increasing the probability of dropping out of school. And than, financial assistance variable were the only variable examined and had a significant effect on reducing the probability of dropping out. The Suggestion in this study is to provide knowledge about the importance of education as a future investment and provide reguler counseling to students. They should not involve their children too much to help with the work of the parent. Then from the government, through optimizing financial assistance.